Impact of dietary plant protein levels on the consumer acceptability of senegalese sole (Solea senegalensis Kaup, 1858) - Pereira, L. (2013)
The aim of the present work was to assess the impact of different vegetable diets in the sensory acceptability of Senegalese sole.